Facing the crises : Anglophone literature in the postmodern world - Matek, Ljubica; Rehlicki, Jasna Poljak (Cambridge Scholars Publishing, 2014)
Owing to the diverse research interests of the contributors, this collection of essays offers a varied picture of the current approaches to Anglo-American literature and culture, and points to the need for a deeper understanding of current cultural, economic and social processes in the globalizing and globalized culture of the West. Because ""crisis"" seems to be the key word of contemporary Western culture, the first part of the book, titled ""In the Face of Crises"", explores the implicit or ...